2007
DOI: 10.1097/mat.0b013e318050d210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous and Pulsatile Flow Left Ventricular Assist on Pulsatility in a Pediatric Animal Model of Left Ventricular Dysfunction: Pilot Observations

Abstract: Pediatric ventricular assist devices are being developed that can produce pulsatile flow (PF) or continuous flow (CF). An important aspect of choosing between these two modes is understanding the consequences of each mode on pediatric vascular pulsatility. Differences in vascular pulsatility generated by PF and CF operation of the 3-inch pediatric cardiopulmonary assist system (pCAS, Ension, Inc., Pittsburgh, PA) were investigated while providing left atrium-to-aorta left ventricular assist (LVA), using an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…In addition to being of interest to basic vascular biology, these types of studies would be useful in evaluation of the relative merits of pulsatile versus steady flow in left ventricular assist devices currently under development. 15,29 In this study, we examined EC gene expression under arterial levels of steady shear stress (SSS) and pulsatile shear stress (PSS) characteristic of the common carotid artery. Transcriptional profiles of the entire genome were generated, hierarchically clustered, and statistically organized according to associated functions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being of interest to basic vascular biology, these types of studies would be useful in evaluation of the relative merits of pulsatile versus steady flow in left ventricular assist devices currently under development. 15,29 In this study, we examined EC gene expression under arterial levels of steady shear stress (SSS) and pulsatile shear stress (PSS) characteristic of the common carotid artery. Transcriptional profiles of the entire genome were generated, hierarchically clustered, and statistically organized according to associated functions.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Augmenting aortic pressure pulsatility via CF LVAD flow and/or motor speed modulation algorithms has been proposed to minimize adverse events, prevent aortic insufficiency, alter ventricular unloading, reduce myocardial oxygen consumption, and improve myocardial recovery. [10][11][12][13][14][15][16][17][18][19][20][21] The potential hemodynamic benefits of CF LVAD modulation evaluated in a computer simulation model with candidate pump speed modulation algorithms identified for feasibility testing. 22 Based on these findings, hemodynamic performance of a clinically approved CF LVAD operated at constant pump speed, and asynchronous, synchronous copulsation, and synchronous counterpulsation modulated pump speed were further investigated in a mock flow loop model, and acutely in a chronic ischemic heart failure (IHF) bovine model (n = 3) to demonstrate feasibility.…”
mentioning
confidence: 99%
“…In an in vivo study of PVAD support in infant piglet models, it was shown that 3 times greater pulsatility was achieved under pulsatile bypass compared to continuous bypass [46]. In the previously discussed pediatric CFD study [27], pulsatility was 2 times greater at the aortic inlet with pulsatile support and between 3.3 and 4.1 times greater at the aortic branches and descending aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Scaled plug flow velocity waveforms were acquired from an in vivo study of PVAD function in infant animal models [46] and scaled to represent a cardiac output (CO) of 1 L/min and a heart rate of 120 beats per minute (bpm). Case 1 represents a healthy pediatric aortic inflow (Fig.…”
Section: Methodsmentioning
confidence: 99%